The end of the beginning for the geographies of religion? - WOODS, Orlando (Institutional Knowledge at Singapore Management University, 2024)
While the geographies of religion have always been a small and relatively niche subfield within (primarily) social and cultural geography, so too has it developed a vibrancy and unique set of characteristics that set it apart from other social scientific and humanistic approaches to the study of religion. From foregrounding the characteristics of religion in/and space, it has since adopted a more expansive, and arguably relaxed, understanding of how an understanding of what might be “geographical” inflects upon what might be “religious” or “secular.” This expansiveness reflects the maturation of the subfield, and its confidence in reaching out beyond disciplinary norms to instead stretch our understandings of both “geography” and “religion” in new and sometimes innovative directions. As we look ahead to further growth within the subfield, there is a need to take stock of where we have come from, where we are now, and where we might be going. To meet this need, the Handbook of the Geographies of Religion is a first-of-its kind reference for those wanting to understand the origins, the defining themes, and the outlook and positioning of the subfield within the broader humanities and social sciences. Comprising 70 chapters from scholars who have shaped, or who will shape the future of the subfield, this Handbook makes the bold claim that it is the end of the beginning for the geographies of religion. In this vein, as much as it is designed to be a one-stop resource for students, researchers, policymakers, and religious personnel seeking to understand the current state of the subfield, so too does it hope to draw a line in the sand, to acknowledge the progress made so far, but also to gesture toward new directions that might shape the subfield in the years to come.